Ethnobotany, floristic and phytochemical studies of medicinal plants used to treat uterine fibroids in Mbarara City, Uganda - Calton Nantinda; Esther Lynnet Kisakye; David Musana; Isaac Ssessanga; Ukashar Ssenabulya; Timothy Omara; Ivan Kahwa; Florence Nalimu (Phytomedicine Plus)
Uterine fibroids (UF) are the most common non-cancerous benign gynaecologic tumours in premenopausal females. In Uganda, the prevalence of UF is estimated at 20%, and several risk factors have been identified as contributing to this prevalence. This study aimed to document the ethnobotanical knowledge of traditional medicine practitioners (TMPs) in Mbarara City, Southwestern Uganda on the use of medicinal plants for UF management. The TMPs play a vital role in the healthcare within this region, often incorporating conventional diagnostic methods such as ultrasound scans before providing herbal treatments. To achieve the study aim, data was collected from April 2024 to May 2024 using structured questionnaires administered. Twenty-six (26) respondents were selected using purposive and snowball sampling techniques. Data were gathered on sociodemographic characteristics, treatment-seeking behaviour, and use of herbal formularies for treatment of UF. Statistical analysis involved descriptive statistics, and computation of the frequency of citation, relative frequency of citation and fidelity level. Our results indicated that most TMPs knew about UF and valued conventional means of diagnosis before initiating herbal treatment. Forty-seven (47) plant species belonging to 32 families and 45 genera were identified. Fabaceae (10.6%), Asteraceae, Lamiaceae (8.5% each), Asparagaceae and Cucurbitaceae (6.4% each) were the most ordinary families. At the same time, Oxygonum sinuatum, Hoslundia opposita, Opuntia ficus-indica, Sesamum angustifolium, Phyllathus niruri, Ricinus communis, Erythrina abyssinica and Leonotis nepetifolia were the most frequently cited species. Leaves (47.6%), stems (17.5%) and flowers (9.5%) of herbs (61.7%), trees (23.4%) and shrubs (14.9%) were the primarily utilized plant parts for preparing decoctions that are administered orally (94%). Classical phytochemical screening of plant organs from the eight most cited species indicated flavonoids, phytosterols, terpenoids, saponins and alkaloids. With initial evidence of the bioactive secondary metabolites, this study underscores the need for further bioassay-guided studies to isolate and characterize bioactive molecules associated with the anti-fibroid efficacy of the species.